The Influence of Ramadan Fasting on Some Hematological and Biochemical Parameters in Healthy Adult Males - mohammed, Zahid (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): Ramadan is the Holy month of the Muslims, where they are required to abstain from food and drinks from dawn till the beginning of night. This study was conducted in Ramadan to investigate the effect of fasting on hematological incidences, lipid profile, renal and liver function tests among healthy adult males. Methodology: The present study was carried out in Ramadan – 1431 of Higira (August-September 2010). The study sample was 56 healthy adult males. Five samples of blood were taken at five intervals (Before, at day 1, 15, 28 and after Ramadan). Estimation was done for hematological markers, (hemoglobin, white blood cells count, platelet count); renal function tests (blood urea, serum uric acid, serum albumin, total serum protein); biochemical parameters, (blood glucose, total serum cholesterol, serum triacylglyceride, high and low density lipoproteins) and liver function tests (AST, ALT, Alkaline phosphatase, total serum bilirubin). Results: The mean age of the subjects was 48.4 years (SD 7.15) and mean weight was 79.92 kg (SD 7.94). No significant changes were observed in weight, hemoglobin, white blood cell count and platelets count, blood urea and serum albumin values. Whereas, serum uric acid and total serum protein levels were statistically lower during and aŌer Ramadan (P< 0.05, 0.01). Blood levels of glucose showed no significant decrease and serum cholesterol and serum triacylglyceride results were non-significant at first 2 weeks of Ramadan. The same significant changes (p< 0.05, 0.01) were observed in the lipoprotein at day 15 and 28 of Ramadan. Findings of liver functions levels showed significant changes. While, total serum bilirubin still with no significant changes during Ramadan. Recommendations: The present study recommends performing more studies with both larger groups and in various categories of healthy and unhealthy subjects.